Determiner removal in Balinese nonpivot agents. (20th May 2022) - Driemel, Imke; Tebay, Sören E.
Abstract: Patient‐voice clauses within the symmetric voice system of Balinese disallow any extraction from the external‐argument position, while definite external arguments are blocked from occurring altogether. The former fact is traditionally taken as evidence for syntactic ergativity in Austronesian. The latter fact has recently been argued to provide evidence for postsyntactic case licensing via adjacency with the verb. In this article, we offer a simple alternative explanation for the in‐situ properties of patient‐voice agents in Balinese—one that does not make reference to case. We argue that patient‐voice heads come with a feature that triggers removal of the external argument's DP shell, resulting in the loss of a determiner and a category‐D feature that would otherwise enable extraction.